International Women's Day 2022 newsletter - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
On International Women’s Day 2022, we highlight how women and girls in agriculture and food systems are contributing to a sustainable tomorrow – in particular by playing important roles in climate change adaptation, mitigation and response.